VISUAL MYTHOLOGY REYOG PONOROGO IN ARTIFICIAL INTELEGENT - Nugroho, Oki Cahyo; Tricana, Deny Wahyu; Pinaryo, Pinaryo; Lestarini, Niken (Universitas Pendidikan Nasional, 2024)
Reyog Ponorogo is an artwork with a rich history and folklore, as well as a particular visual narrative that is worth studying through the lens of visual data studies. Reyog performers offer significant meanings via the visuals of their performance as well as the ideology of Ponoragan Javanese culture. The purpose of this project is to convert oral myths into visual signals in Reyog performances using visual data. Using W.J.T. Mitchell's